2018
DOI: 10.1016/j.jad.2018.08.070
|View full text |Cite
|
Sign up to set email alerts
|

The association between gestational diabetes mellitus and postpartum depressive symptomatology: A prospective cohort study

Abstract: Women with GDM may be at increased risk of PPDS. Future studies should investigate whether these women would benefit from a closer follow-up and possible supportive interventions during pregnancy and the postpartum period to avoid PPDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
(48 reference statements)
1
24
3
Order By: Relevance
“…As a result, without continued psychosocial support from health services and family in the postpartum period, women feel abandoned and in limbo, which hinders their ability to maintain health behaviour changes. Finnish and American studies have found a significant association between GDM and postnatal depression using the validated Edinburgh Postnatal Depression Scale [11,49]. Only one woman in our study reported having postnatal depression following the GDM pregnancy and similar studies from LMIC are still lacking.…”
Section: Experience Of Gdm Deliverycontrasting
confidence: 64%
See 2 more Smart Citations
“…As a result, without continued psychosocial support from health services and family in the postpartum period, women feel abandoned and in limbo, which hinders their ability to maintain health behaviour changes. Finnish and American studies have found a significant association between GDM and postnatal depression using the validated Edinburgh Postnatal Depression Scale [11,49]. Only one woman in our study reported having postnatal depression following the GDM pregnancy and similar studies from LMIC are still lacking.…”
Section: Experience Of Gdm Deliverycontrasting
confidence: 64%
“…Interestingly, women with GDM in an Italian study reportedly experienced a better quality of life, compared to pregnant women without GDM [ 7 ] as a result of the improved health behaviours. Considering that among low-income women in South Africa, the experience of at least one stressful event can impact on maternal mental health [ 25 ], risk surveillance for mental health disorders, close monitoring and tailored programmes to reduce perceived emotional distress may have benefits for the overall well-being of women with GDM [ 10 , 11 , 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational weight gain and Caesarean delivery, both complications of GDM, were particularly strongly associated with postpartum depressive symptoms , suggesting that increases in body weight may be an important mediator in those cases where GDM does predate depressive symptoms. One study did report an association between GDM and postpartum depression that was not explained by Caesarean delivery, although gestational weight gain was not measured in this study .…”
Section: Introductionmentioning
confidence: 80%
“…Antenatal events and social circumstances, such as disease during pregnancy, family dissatisfaction or social isolation, have also been identi ed as risk factors for postnatal depression [11,20]. Maternal depressive symptoms and events in the antenatal period are strongly associated with postnatal depressive symptoms and numerous adverse perinatal outcomes including preterm delivery and low birth weight [19,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%